Three-Component Reaction of 3-Arylidene-3H-Indolium Salts, Isocyanides, and Alcohols - Golantsov, Nikita E.; Nguyen, Hung M.; Golubenkova, Alexandra S.; Varlamov, Alexey V.; Van der Eycken, Erik V.; Voskressensky, Leonid G. (Frontiers in Chemistry, 2019)
A novel isocyanide-based multicomponent synthesis of alkyl aryl(indol-3-yl)acetimidates has been established. Starting from aryl(indol-3-yl)methylium tetrafluoroborates, aromatic isocyanides and alcohols, the imidates were obtained in moderate to very good yields. Consecutive four-component synthesis of the above mentioned imidates from N-alkylindoles, aromatic aldehydes, aromatic isocyanides and alcohols was also proposed. In addition, it was shown that in the presence of water, aryl(indol-3-yl)methylium tetrafluoroborates reacted with isocyanides to furnish aryl(indol-3-yl)acetamides